Penerapan Metode Agile dan Technology Acceptance Model (TAM) Pada Sistem Informasi Pelayanan Olla Studio.ID - Dwiyola Agnesia; Kirman; Yetman Erwadi (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2025)
The development of information technology has encouraged creative service businesses such as Olla Studio.ID to adopt information systems to support service processes and operational management. This research aims to develop a service information system using the Agile (Scrum) method that is iterative and flexible to changing user needs. Development is carried out through three sprint cycles, starting from needs analysis, design, implementation, to evaluation. To measure the level of user acceptance of the developed system, the Technology Acceptance Model (TAM) approach is used with two main variables, namely Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). The evaluation results showed that the information system developed received a positive response from users, with a PU value of 65% and PEOU of 60% in the “Strongly Agree” category. The application of Agile methods proved effective in adapting the system to user needs, and evaluation using TAM showed the system was well received by Olla Studio.ID staff and customers. This research shows that the combination of Agile and TAM can be used as a strategic approach in building and evaluating adaptive and user-friendly information systems. Keywords— Agile, Information System, TAM, Perceived Usefulness, Perceived Ease of Use